2021
DOI: 10.3390/en14164737
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Processing Factors in Two-Step Fabrication of Pure Sulfide CIGS Absorbers

Abstract: Pure sulfide CIGS solar cells are interesting candidates for standalone solar cells or top cells in a tandem configuration. To understand the limits and improve the power conversion efficiency of these devices, a comprehensive approach aimed at composition, interface, and process engineering should be employed. Here, the latter was explored. Using a two-step fabrication technique and one-variable-at-a-time methodology, we found the four processing factors affecting the absorber the most. While two were already… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The band gap of the CIGSe 2 material group can be adjusted between 1.0-1.7 eV, whereas the band gap of the CIGS 2 material group can be modified between 1.5-2.4 eV [5,6]. A variation of CIGSe 2 materials with the band gap in the narrower range is suitable for the bottom cell application [7], while the wider band gap CIGS 2 materials are suitable for the top cell application [8]. In addition to that, the band gap of low-Ga CIGS 2 is also very close to the ideal single-junction solar cell band gap for the best spectral matching application [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The band gap of the CIGSe 2 material group can be adjusted between 1.0-1.7 eV, whereas the band gap of the CIGS 2 material group can be modified between 1.5-2.4 eV [5,6]. A variation of CIGSe 2 materials with the band gap in the narrower range is suitable for the bottom cell application [7], while the wider band gap CIGS 2 materials are suitable for the top cell application [8]. In addition to that, the band gap of low-Ga CIGS 2 is also very close to the ideal single-junction solar cell band gap for the best spectral matching application [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…While a pure selenide absorber layer demonstrated 22.6 % record efficiency [2], devices based on pure sulfides remains lower with a 15.5 % record efficiency achieved using an absorber with a bandgap below 1.6 eV [3]. Nevertheless, by combining both improved material properties and growth process understanding, several groups have shown improved performance launching pure sulfide based devices towards much higher efficiency [4,5]. Moreover, the bandgap of CuIn 1-x Ga x S 2 can be tuned between 1.5 eV and 2.4 eV by increasing x from 0 through 1 [6].…”
Section: Introductionmentioning
confidence: 99%
“…In this method of making these types of chalcogenide absorber layers, essentially a metal precursor of copper-gallium and indium is selenized (and/or sulfurized) with a solid or gaseous source. Next to valuable insights from the work of Intermolecular [6], some clarity on processing of pure selenide and pure sulfide variations of these chalcogenides has been recently offered by Solliane and imec, respectively [7,8]. On the other hand, as Kato et al suggested [9], every tool and fabrication design might need its own process optimization for best results.…”
Section: Introductionmentioning
confidence: 99%